2023
DOI: 10.1080/12298093.2023.2272380
|View full text |Cite
|
Sign up to set email alerts
|

Determining Potential Link between Environmental and Clinical Isolates of Cryptococcus neoformans/Cryptococcus gattii Species Complexes Using Phenotypic and Genotypic Characterisation

Kenosi Kebabonye,
Mosimanegape Jongman,
Daniel Loeto
et al.

Abstract: Opportunistic infections due to Cryptococcus neoformans and C. gattii species complexes continue to rise unabated among HIV/AIDS patients, despite improved antifungal therapies. Here, we collected a total of 20 environmental and 25 presumptive clinical cryptococcal isolates from cerebrospinal fluid (CSF) samples of 175 patients enrolled in an ongoing clinical trial Ambition 1 Project (Botswana-Harvard Partnership). Identity confirmation of the isolates was done usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…One Denmark study reported the combination of AFLP with multilocus sequence typing (MLST of nuclear loci including LAC1, CAP59, IGS1, PLB1, URA5, SOD1, and GPD1). Selected Cryptococcus isolates subsequently underwent antifungal susceptibility testing and a comparison with isolates across the world [30]. Similarly, the AFLP and MLST methods were utilized for subsequent multilocus microsatellite typing (MLMT) and phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One Denmark study reported the combination of AFLP with multilocus sequence typing (MLST of nuclear loci including LAC1, CAP59, IGS1, PLB1, URA5, SOD1, and GPD1). Selected Cryptococcus isolates subsequently underwent antifungal susceptibility testing and a comparison with isolates across the world [30]. Similarly, the AFLP and MLST methods were utilized for subsequent multilocus microsatellite typing (MLMT) and phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%